A contemporary analysis of aircraft maintenance-related accidents and serious incidents - Insley, Jennifer; Turkoglu, Cengiz (MDPI, 2020)
Aircraft maintenance has been identified as a key point of concern within many high-risk areas of aviation; still being a casual/contributory factor in a number of accidents and serious incidents in commercial air transport industry. The purpose of this study is to review and analyse the aircraft maintenance-related accidents and serious incidents which occurred between 2003 and 2017, to provide a better understanding of the causal and contributory factors. To achieve this, a dataset of maintenance-related accidents and serious incidents was compiled and then qualitatively analysed by thematic analysis method. Coding these events by using NVivo software enabled the development of a taxonomy, MxFACS. The coded output was then evaluated by subject matter experts, and an inter-rater concordance value determined to demonstrate the rigour of the research process. Subsequently, the events were evaluated in terms of their relationship to known accident categories such as loss of control, runway excursions. The most frequent maintenance event consequences were found to be runway excursions and air turnbacks, with the second level categories being related to failures in engine and landing gear systems. The greatest maintenance factor issues were ‘inadequate maintenance procedures’ and ‘inspections not identifying defects’. In terms of fatalities, ‘collision events’ were the most prominent consequence, ‘engine-related events’ were the most significant event, and ‘inadequate maintenance procedures’ were the most concerning maintenance factor. The study’s findings may be used in conjunction with existing risk analysis methodologies and enable the stakeholders to develop generic or customised bowties. This may identify the existing barriers in the system as well as weaknesses which will enable the development of mitigation strategies on both organisational and industry-wide levels.
Keywords: flight safety; aviation accidents; airworthiness; aircraft maintenance; MxFACS